Independient virtual english language learning: a case study in higher education - Esther Nieto Moreno de Diezmas; Mª Victoria Guadamillas Gómez; Mª Prado García-Cano Lixcano (Universidad de Málaga, 2016)
The development of independent and self-learning strategies for Foreign Language Learning is of special interest in Higher Education. In particular, these strategies are essential in the Foreign Language Learning area (EFL), since students need to practise and strengthen their exposure to language so as to develop receptive and productive skills. The goal of this paper is to show how independent and virtual learning are developed by means of ICT. To this end, a group of tasks and activities have been designed, distributed and implemented by means of Moodle in the setting of a teaching innovation project in which different campuses and faculties of Education of the University of Castilla-La Mancha where English I is studied have taken part. Additionally, the initial results in terms of students' perceptions about their independent and virtual learning are shown. Therefore, this paper focuses on a case study at Higher Education in which valid conclusions may be drawn for other similar settings where language learning and virtual learning need to be combined. Initial results suggest the students have responded positively in terms of their perception and participation. This validates the tasks and procedures carried out in the implementation of virtual foreign language learning.